The perfect horse ebook The daring u.s. mission to rescue the priceless stallions kidnapped by the nazis. - Letts, Elizabeth (2016)
NEW YORK TIMES BESTSELLER • From the author of The Ride of Her Life and The Eighty-Dollar Champion comes the “winningly readable” ( The Christian Science Monitor ) true story of the heroic rescue of priceless horses in the closing days of World War II. “Hard to put down . . . One need not be an equestrian or horse lover in order to appreciate this story.”— New York Journal of Books WINNER OF THE PEN AWARD FOR RESEARCH NONFICTION   In the chaotic last days of the war, a small troop of American soldiers captures a German spy and makes an astonishing find—his briefcase is empty but for photos of beautiful white horses that have been stolen and kept on a secret farm behind enemy lines. Hitler has stockpiled the world’s finest purebreds in order to breed an equine master race. But with the starving Russian army closing in, the animals are in danger of being slaughtered for food.   With hours to spare, one of the U.S. Army’s last great cavalrymen, Colonel Hank Reed, makes a bold decision—with General George Patton’s blessing—to mount a covert rescue operation. Racing against time, Reed’s determined force of soldiers, aided by several turncoat Germans, steals across enemy lines to save the horses.   An exhilarating tale of adventure, courage, and sacrifice, The Perfect Horse brings to life one of the most inspiring chapters in the annals of human valor.